Smart Homes: Steps, Components, Utilities and Challenges - Gopinath, Velivela; Srija, Arigela; S Krishna Rao, Dr; Madhuri, Avula (International Journal of Engineering and Technology, 2018)
Smart Home is a flourishing technology of 20th century. It integrates of many new technologies through home networking for improving quality of humanâ€™s life. Intelligent Home trade has drawn goodish attention of researchers for quite a decade. Smart Home technology is a combination of network and services and much more consequently, this paper focuses on various topics in smart home technologies from surveying for smart home research projects and presents a survey of all such systems and covers advantages of smart home systems, smart steps and simple components to install smart homes. So, the presented paper can be cookbook of ideas for who ever want to learn this blossoming technology.Â Â
Keywords: Smart Home; Sensors; Smart Home Appliances; Home Automation and Smart Home Technologies.